Medium optimization for leaf numbers and shoot multiplication of lidah buaya (Aloe vera) by BAP and adenine supplement - LAELA SARI (Society for Indonesian Biodiversity, 2005)
Aloe vera of the Aloeaceae is originated from Canary Island (West Africa). This plant is commonly know in Indonesia and cultivated in large fields or in the house yard for many purposes, such as ornamental and medicine plant. The industries using it as the principle raw material has became more important due to the significant benefits of this plant. This study is purposed to obtain the medium optimization for leafnumbers and shoot multiplication of Aloe vera by BAP and adenine supplement. The shoot of Aloe vera was taken from green house of Biotechnology-LIPI. Shoots sterilized by clorox (sodium hypochlorite) solution 35% and 20% for 30 and 15 min. until get aseptic shoot (in vitro plants). The shoot isolated from in vitro plant into MS (Murashige and Skoog) medium in different concentration of BAP and adenine. The research used factorial Completely Randomized Design with two factors (BAP concentration: 0; 0.5; 1; 1.5; 2 mg/L and adenine concentration 0; 10; 20 mg/L) with 5 replicates. The results obtained have showed that addition 20 mg/L adenine to MS raise the numbers of leaf. The shoot multiplication has been augmented by addition of BAP 1 mg/L and adenine 20 mg/L. The results showed that BAP has a positive role in increasing shoot multiplication rate and that adenine has a synergic effect when added together with BAP.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: optimization, Aloe vera, BAP, adenine, in vitro tissue culture.